Localised Mobile Learning Solutions: Responding to the Needs of Global Education - Aarreniemi-Jokipelto, Päivi; Goulart, Elias E. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.374, 2017)
Mobile phone penetration has increased considerably throughout the world, and it reached 142% in Brazil in 2015. In addition to the strong trend of mobile device usage in free time, there has been an increase in use for learning purposes. Mobile devices can deliver learning to people, communities, and countries where other educational inventions have been too expensive, difficult, dangerous, or demanding. The objective of the present study was to test if existing e-learning solutions could be localised to enable mobile learning in Brazil. Another aim of the study was to develop a mobile learning taxonomy defining the criteria for localising mobile learning in global education, to tailor it to different circumstances and cultures.